Handheld raman spectrometer for the rapid determination of synthetic cannabinoids - Ling Zhang; Guoping Li (Wolters Kluwer Medknow Publications, 2019)
A handheld laser Raman spectrometer was developed to detect 11 synthetic cannabinoid standards. The spectrometer can be connected with a mobile phone by Bluetooth or a computer by a data cable. The Raman spectra of the synthetic cannabinoids AM-694, JWH-019, and nine others were accurately determined by software analysis of characteristic Raman peaks. This technique is highly efficient, accurate, and simple, and it is a valid procedure for rapid on-site investigations of cannabinoids.